PatientViewpoint: A Website for Patient-Reported Outcomes Assessment - Snyder, Claire F. (2009)
PURPOSE: To develop a prototype website to collect patient-reported outcomes (PROs) in outpatient clinical oncology and link the data with the electronic medical record (EMR). METHODS: A multidisciplinary Research Network, including experts in outcomes research, clinical oncology, nursing, social work, information technology, EMRs, behavioral science, decision science, clinical trials, law, and a cancer survivor, was formed to design the prototype website. The Research Network developed the initial website specifications, elicited feedback from patients (n=20) and clinicians (n=7), constructed the website, and conducted usability testing (n=10). RESULTS: Clinicians reported that the website could improve clinical practice if it was not burdensome and were most interested in tracking change over time. Patients were interested in using the website because of the potential to facilitate communication with their clinicians. Patients emphasized the importance of short and simple surveys and a user-friendly interface. The PatientViewpoint website was designed to meet these specifications. Usability testing suggested that patients had few problems accessing and using the site. CONCLUSIONS: Preliminary reports from clinicians and patients suggest that a website to collect PROs and link them with the EMR could help improve the quality of cancer care. Further pilot-testing will evaluate the use, usefulness, and acceptability of PatientViewpoint.